Agro-industrial wastewater in a circular economy: Characteristics, impacts and applications for bioenergy and biochemicals. (December 2021) - Martinez-Burgos, Walter José; Bittencourt Sydney, Eduardo; Bianchi Pedroni Medeiros, Adriane; Magalhães, Antonio Irineudo; de Carvalho, Júlio Cesar; Karp, Susan Grace; Porto de Souza Vandenberghe, Luciana; Junior Letti, Luiz Alberto; Thomaz Soccol, Vanete; de Melo Pereira, Gilberto Vinícius; Rodrigues, Cristine; Lorenci Woiciechowski, Adenise; et al.
Graphical abstract: Highlights: Agro-industrial effluents have significant environmental impacts. Large volumes of agro-industrial effluents are generated worldwide by agro-industries. Bioenergy is the most promising way to valorize agro-industrial wastewater. Obtaining biometabolites from effluents is an alternative to increase profitability. Abstract: The generation of agroindustrial byproducts is rising fast worldwide. The slaughter of animals, the production of bioethanol, and the processing of oil palm, cassava, and milk are industrial activities that, in 2019, generated huge amounts of wastewaters, around 2448, 1650, 256, 85, and 0.143 billion liters, respectively. Thus, it is urgent to reduce the environmental impact of these effluents through new integrated processes applying biorefinery and circular economy concepts to produce energy or new products. This review provides the characteristics of some of the most important agro-industrial wastes, including their physicochemical composition, worldwide average production, and possible environmental impacts. In addition, some alternatives for reusing these materials are addressed, focusing mainly on energy savings and the possibilities of generating value-added products. Finally, this review considers recent research and technological innovations and perspectives for the future.